Penerapan Akulturasi Islam dan Budaya dalam Tradisi Munggah Muluh Suku Jawa di Wilayah Stabat - Dani Kesuma; Jufri Naldo; Kasron Munchsin (IAI Nasional Laa Roiba Bogor, 2024)
The vast territory of Indonesia stretches from Sabang to Merauke and from Miangas Island to Rote Island. Apart from its vast land and abundant natural resources, Indonesia also has a very diverse culture, this can be seen from the disparities in race, religion, ethnicity and inter-group (SARA. Using a qualitative approach method, the researcher wrote this scientific paper. The study's findings indicate that individuals have greater faith in every item in the Munggah Muluh procession. The blending of local knowledge with the Islamic faith led to the acculturation of Islam and Javanese culture in the Munggah Muluh tradition, resulting in the creation of several customs rather than just one. Islam and local communities' teachings, like Selamatetan, which was once a local culture before evolving and appearing to become a shared culture since in reality both aspects of Islam and local wisdom meld into one, are examples of this blending.